BMPR-II, caspase-3, HIF-1α, and VE-cadherin profile in Down syndrome children with and without congenital heart disease and pulmonary hypertension - Widjaja, Sri L.; Anniazi, Masayu L.; Artiko, Bagus; Moelyo, Annang G.; Ahmadwirawan, Mylco T. (Narra J, 2025)
Several cellular markers have been identified as effective in detecting vascular remodeling recently. The reduced activity of bone morphogenetic protein receptor type-II (BMPR-II), commonly observed in Down syndrome, results in insufficient production of vascular endothelial cadherin (VE-cadherin). This, in turn, increases hypoxia-inducible factor-1α (HIF-1α) levels and leads to excessive production of caspase-3. The aim of this study was to compare the plasma levels of BMPR-II, VE-cadherin, HIF-1α, and caspase-3 between pediatric Down syndrome with and without congenital heart disease (CHD) and pulmonary hypertension (PH). This was to investigate the role of these biomarkers in the pathogenesis of PH associated or not associated with CHD. A cross-sectional study was conducted on Down syndrome children aged two months to five years at a tertiary hospital between January and December 2023. The children were classified into four groups: CHD with PH, CHD without PH, non-CHD with PH and normal heart. Plasma levels of BMPR-II, caspase-3, HIF-1α, and VE-cadherin were measured using ELISA and compared based on the presence or absence of CHD and PH using Kruskal-Wallis followed by post hoc Bonferroni tests. Elevated plasma HIF-1α levels were observed in all patients with PH, with significantly higher levels in those with CHD-PH. Elevated levels of caspase-3 were also observed among children with PH groups, with the highest levels observed in the non-CHD PH group. Plasma levels of BMPR-II and VE-cadherin were elevated in PH, with significantly higher levels in the non-CHD PH group compared to other groups.